2018
DOI: 10.12973/iji.2018.11437a
|View full text |Cite
|
Sign up to set email alerts
|

Open Inquiry in Facilitating Metacognitive Skills on High School Biology Learning: An Inquiry on Low and High Academic Ability

Abstract: Learning model and academic ability are important considerations in developing students' skills including metacognitive skills in biology learning. The study aimed to investigate the effect of open inquiry on the metacognitive skills of students in different academic abilities. The study was quasi-experimental research, using the equivalent post-test only with control group design. The subjects of the experiment comprised 60 eleventh grade students. The samples were randomly assigned in a 2x2 factorial design.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 11 publications
1
14
1
7
Order By: Relevance
“…al., 2019) and open inquiry learning was more potential to facilitate high metacognitive skills in high and low academic abilities of students rather than conventional method. The interaction of the learning models and academic abilities in this study showed no significant difference of metacognitive skills (Rahmat & Chanunan, 2018).…”
Section: Article Historycontrasting
confidence: 50%
See 2 more Smart Citations
“…al., 2019) and open inquiry learning was more potential to facilitate high metacognitive skills in high and low academic abilities of students rather than conventional method. The interaction of the learning models and academic abilities in this study showed no significant difference of metacognitive skills (Rahmat & Chanunan, 2018).…”
Section: Article Historycontrasting
confidence: 50%
“…Practicum is an important activity in order to support understanding of the concepts that have been previously studied in class (Damopolii, Nunaki, Nusantari, & Kandowangko, 2020;Rahmat & Chanunan, 2018). Based on the observations made, the practicum activities currently taking place are still using conventional practicum guides such as directions in the recipe book.…”
Section: Article Historymentioning
confidence: 99%
See 1 more Smart Citation
“…If we look at the results obtained from LPCUT in general, the OIBL in the experimental group and the science program instruction in the control group led to an increase in the scientific response rate of the students in both groups. In the studies, it was similarly found that inquiry based instruction was effective on students' conceptual understanding (Anderson, 2002;Rahmat & Chanunan, 2018;Şimşek & Kabapınar, 2010;Ucar & Trundle, 2011). In this study, the scientific response rates of the students in both groups increased AI and this is a desired result.…”
Section: Conclusion and Discussionmentioning
confidence: 49%
“…(2015) menyatakan bahwa aktivitas belajar siswa yang ibelajarkan menggunakan metode inquiry terbimbing lebih tinggi daripada menggunakan konvensional. Rahmat & Chanunan (2018) juga menyatakan bahwa penerapan pembelajaran inquiry merupakan strategi yang efektif dimana dapat menjembatani perbedaan kemampuan akademik di antara siswa sehingga bisa mencapai target yang diharapkan.…”
Section: Peningkatan Prestasi Belajar Siswa Kelas VII Smps Katolik St Aloysius Wolotopo Dengan Menerapkan Model Pembelajaran Inquiryunclassified